2012
DOI: 10.1111/j.1447-0756.2012.01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of microRNA‐34a in the pathogenesis of placenta accreta

Abstract: Expression of miR-34a was downregulated in placenta accreta. In vitro experiments also showed that the invasive potential of JAR increased by suppressing miR-34a, probably through the expression of PAI-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…Studies on human placental choriocarcinoma human placental choriocarcinoma cells (JAR) revealed that miR-34a represses Notch1, Jagged 1, Serpina-3 and possibly plasminogen activator inhibitor-1 and restricts cell invasion capacity [40][41][42].…”
Section: Invasion and Migration Of The Trophoblastsmentioning
confidence: 99%
“…Studies on human placental choriocarcinoma human placental choriocarcinoma cells (JAR) revealed that miR-34a represses Notch1, Jagged 1, Serpina-3 and possibly plasminogen activator inhibitor-1 and restricts cell invasion capacity [40][41][42].…”
Section: Invasion and Migration Of The Trophoblastsmentioning
confidence: 99%
“…Several studies reported possible molecular or genetic changes in PAS compared to normal controls, such as MMP2 might be increased in placenta percreta [23], or MicroRNA-34a might be decreased in placenta accreta [29], but they only compared the genetic changes between cases and controls in groups. In this study, the CTSV staining pattern in EVT was compared between the adherent site and the non-adherent site within identical cases, and the pattern was found to differ according to the adhesion status where EVT was located.…”
Section: Discussionmentioning
confidence: 99%
“…Many other detection methods have been applied to miRNA studies, such as Northern blot analyses [22,57], quantitative real-time PCR [19,22,82], microarrays [21,26,57,83] and in situ hybridization (ISH) [12,84]. Northern blot assays are used, not only to detect the levels of miRNAs, but also to provide insightful information on the distribution of individual miRNA precursors in different tissues.…”
Section: Expression Of Mirnas In Human Placentamentioning
confidence: 99%
“…Several miRNAs, including miR-210 [105], miR-34a [84,131] and miR-29b [23,84] have inhibitory effects on trophoblast cell invasion. It was reported that miR-210 inhibited the migration and invasion capability of trophoblast cells by repressing Ephrin-A3 and Homeobox-A9 [105].…”
Section: Regulation Of Placental Development and Function By Mirnasmentioning
confidence: 99%
See 1 more Smart Citation